Agricultural population urbanization, long-run economic growth, and metropolitan electricity consumption: An empirical dynamic general equilibrium model - Yiming He (Energy Strategy Reviews, 2020)
Urbanization is a key component for the sustainable development of affordable and efficient electric services in urban and rural area, driving economic growth and electricity consumption. This paper identifies the causal effects of urbanization and metropolitan economic performance on electricity consumption by a dynamic general equilibrium theoretical framework and time series econometric models using data from 1949 to 2016 in Guangzhou, China. Both autoregressive distributed lag (ARDL) and Johansen cointegration techniques show that electricity consumption, urbanization and metropolitan economic performance are cointegrated. The results of two-stage least squires (TSLS) demonstrate that the marginal propensity to electricity consumption in Guangzhou is about 1.28. To improve the electricity use efficiency, policies should be implemented to transfer the current electricity consumption pattern into a pattern of low energy intensity.